(untitled) (Research, Society and Development, 2023)
The representation of Brazilian indigenous ethnicities and cultures in the textbook of the national program in the teaching of History in the 2nd segment of fundamental education, distributed from 2020 to 2023, at the Kunyata Putira indigenous school, raises salutary questions regarding the possible devaluation of these peoples, hampering the planning and development of attractive activities for students. In this way, the general objective of this study is to analyze ethnic groups and indigenous cultures and how they are represented in the textbook with emphasis on the Municipal Indigenous School Kunyata Putira in the year 2021 to 2022. Methodology. This is a qualitative, exploratory and field bibliographic research. According to the ethnographic research, carried out with indigenous teachers, residents of the community, working at the Kunyata Putira Municipal Indigenous School, located in the São Thomé community, on the left bank of the Rio Negro in Manaus, Amazonas/Brazil, they responded to the survey through the questionnaire, expressed that the indigenous peoples represented in the history textbook used in the pedagogical work in the classroom are: Umbu, Sambiqui, Puris, Guaicuru, Kalapalo, Tapirapé, Paxató, Kamayura, Yanomami, Mondé, Tuparí, Juruna, Mundurukú and Ramarána, Bororo , Ikpeng, Jê, Botocúdo, Karajá, Maxakalí, Aztec, Inca and Maia. It was concluded that the indigenous people of the Kunyata Putira Municipal Indigenous School do not have history books focused on their educational reality and that they study cultures of other indigenous peoples.